Evaluation of Toxic Effect of Phaleria macrocarpa (Scheff.) Boerl Leaf Extract on Hematological Parameters - Q, Hanif M; Y, Yuandani; U, Harahap (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: This current study was conducted to evaluate the toxic effect of P. macrocarpa leaf extract (Phaleria macrocarpa (Scheff.) Boerl) on hematology parameters in rats. Design: The toxicity of ethanol extract of P. macrocarpa leaf was evaluated by OECD guidelines. The extract at doses of 100, 500, 1000 mg/kg body weight (bw), control satellite and satellite group dose 1000 mg/kg bw were orally administered to the test animal for 90 days. Hematological parameters were observed for 90 days and 118 days for treatment and satellite group, respectively. Interventions: The variable that was intervened in this study was the doses of P. macrocarpa extract. Main outcome measure: The main results in this study were the toxic effect of P. macrocarpa leaf on hematology parameters. Results: The etanol extract of P. macrocarpa did not cause any changes in hematological parameters, these include red blood cells (RBC), hemoglobin, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), platelet, white blood cells (WBC), neutrophils, lymphocytes, monocytes, eosinophils, and basophils levels as compared to normal control (P>0.05) Conclusion: The ethanol extract of P. macrocarpa leaf did not cause any toxic effect on hematological parameters for long-term use.